Quality of Diet and Nutritional Status on Male Young Athletes in Central Java - Mardiana, Mardiana; Lestari, Yanesti Nuravianda; Prameswari, Galuh Nita (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Fulfilling energy and nutritional intake that is not in accordance with dietary recommendations and nutritional guidelines will affect the quality of athlete’s diet. Preliminary study results that an average of athlete’s energy consumption only 74% of the recommended energy requirement and 8% athletes are undernutrition. This study aims to evaluate the quality of the diet and sufficiency of energy and nutrition and to determine the relationship with the nutritional status of young male athletes. This study was conducted in 2019. Kind of this study is observational analytic, which using a cross sectional design to 85 young male athletes of the Central Java Student Sports Education and Training Center from 9 kind of sports (takraw, weightlifting, swimming, fencing, basketball, rowing, volleyball, soccer, and athletics). The subjects were measured of their weight, height, fat mass, and waist circumference and then determined their nutritional status (BMI age, body fat percentage, and height ratio). Energy and nutritional sufficiency were obtained by interview using the Semi-Quantitative FFQ, and data of food quality were obtained by using the Diet Quality Indexs International (DQI-I) questionnaire. Data analysis used the Spearman Rank Test with a significance level (α) 0.05 and a confidence level of 95% CI. The results showed that the quality of the foods (p = 0.144; 0362; and 0296), as well as the sufficient energy and nutrients (p = 0.143; 0410; 0608; 0153; 0735; 0836; 0222; 0533; 0326; 0553; 0392; and 0308 ) but they were not related to nutritional status (BMI age, body fat percentage, and WtHR). It was concluded that the quality of the diet was related to energy and nutritional sufficiency, but both of them do not show a significant relationship with the nutritional status of young male athletes of Province of Central Java.